Effect of extender supplemented with date palm pollen grain on bovine semen qualities (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Natural extract from plant-based has grown in popularity as protective properties in extender for preserving animal semen. Date palm pollen grain (DPPG) is commercially used for male fertility by enhancing sperm count, motility and DNA quality because DPPG contains flavonoids. Thus, the present study aimed to evaluate the effect of a) extender supplementation with different concentration of DPPG on sperm motility, viability and membrane integrity b) different preservation storage of chilled and frozen bovine semen after seven days. The semen was collected through electrical stimulation and assigned to four treatment groups. The semen were diluted in Tris citric fructose egg yolk (TCFY) diluent (control group; CG) or supplemented with DPPG with different concentration (G1 = 2%, G2 = 4% and G3 = 6% in 20 mg DPPG/40 mL of Tris citric fructose (TCF). Semen samples were chilled (experiment 1) in the refrigerator (4°C) for seven days and cryopreserved in liquid nitrogen (experiment 2) prior to dilution to four treatments. The samples were thawed in a water bath (37 °C) and analysed for motility, membrane integrity and viability by conventional laboratory methods. No significant difference was observed among treatment groups in experiment 1. However, in the second experiment, the addition of 6% DPPG resulted significantly higher (p
Keywords: cryopreserve; bovine; chilling; frozen; membrane integrity; Tris-citric fructose extender